Orientations and water dynamics of photoinduced secondary charge-separated states for magnetoreception by cryptochrome - Misato Hamada (Nature Portfolio, 2021)
Cryptochromes are photoreceptors involved in biological magnetoreception, but the interplay of conformation, electronic coupling, and molecular motion remains poorly understood. Here, time-resolved electron paramagnetic resonance experiments support a role for hydration dynamics control electronic coupling in a cryptochrome.